2014
DOI: 10.1002/acn3.92
|View full text |Cite
|
Sign up to set email alerts
|

Increased CXCL10 expression in MS MSCs and monocytes is unaffected by AHSCT

Abstract: ObjectiveTo confirm CXCL10 over production in bone marrow mesenchymal stem cells (MSCs) and circulating monocytes isolated from multiple sclerosis patients (MS) and identify predate cell molecular signature; to extend this analysis after autologous hematopoietic stem cell transplantation (AHSCT) to test if therapy has modifying effects on MSCs and circulating monocytes.MethodsMSCs and monocytes were isolated from 19 MS patients who undergone AHSCT before and seven of them at least 3 years after transplant. CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…4 b). A previous study indicated that one of the transcription factors of the PI3K-AKT pathway, CREB, may be involved in the transcription of CXCL10 [ 23 ]. To verify this, we treated CD115(+) precursors with BYL719, GSK690693, 666–15 and rapamycin, which are a PI3K antagonist, AKT antagonist, CREB antagonist and mTOR antagonist, respectively, to test their effects on the expression of CXCL10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 b). A previous study indicated that one of the transcription factors of the PI3K-AKT pathway, CREB, may be involved in the transcription of CXCL10 [ 23 ]. To verify this, we treated CD115(+) precursors with BYL719, GSK690693, 666–15 and rapamycin, which are a PI3K antagonist, AKT antagonist, CREB antagonist and mTOR antagonist, respectively, to test their effects on the expression of CXCL10.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have revealed that the PI3K pathway participates in the regulation of CXCL10 [ 21 , 46 ] and that inhibiting the PI3K pathway downregulates the production of CXCL10 and affects CXCL10 gene promoter activity, which is consistent with the findings of this study. Furthermore, a previous study showed that CREB is involved in the expression of CXCL10 [ 23 ]. Here, we revealed that inhibiting the transcription factor CREB directly can downregulate the expression of CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this include: failure of CXCL10- specific mAbs to inhibit all CXCR3 ligands, inability of anti-CXCL10 mAbs to compete with the high synthesis and turnover rate of CXCL10, and inability of some anti-CXCL10 mAbs to bind the glycosaminoglycan (GAG) bound form of CXCL10 (the active form of CXCL10). Importantly, SLAMF7-mediated inhibition of alpha chemokines has the ability to overcome all of these limitations and may find itself to be a useful therapeutic modality in diseases where over-expression of CXCL10 has been linked to pathogenesis including: rheumatoid arthritis (51), type I diabetes mellitus (52), systemic lupus erythematous (53), multiple sclerosis (54), ulcerative colitis (55), and primary biliary cirrhosis (56).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 expression was significantly increased in bone marrow mesenchymal stem cells (MSCs) and peripheral monocytes of MS, activating its downstream molecules STAT-1, NF-κB, P38, JNK and CREB, increasing the production of CXCL10 and promoting inflammatory responses ( 51 ). Pertussis toxin (PTX), an adjuvant in inducing EAE, depended on TLR4 signaling molecules to facilitate T cell infiltration into the CNS ( 52 , 53 ).…”
Section: Role Of Tlrs In Neuroimmune Diseasesmentioning
confidence: 99%